Labor in the time of Trump - Kerrissey, Jasmine, 1977-; Weinbaum, Alys Eve, 1967-; Hammonds, Clare; Juravich, Tom; Clawson, Dan (Ithaca, New York : ILR Press, an imprint of Cornell University Press, 2019)
"The labor movement has been under attack for decades; by understanding the nature of the right-wing attack, activists and scholars can analyze ways to build a working-class movement in the United States"--
Labor in the Time of Trump critically analyzes the right-wing attack on workers and unions and offers strategies to build a working-class movement. While President Trump's election in 2016 may have been a wakeup call for labor and the Left, the underlying processes behind this shift to the right have been building for at least forty years. The contributors show that only by analyzing the vulnerabilities in the right-wing strategy can the labor movement develop an effective response. Essays in the volume examine the conservative upsurge, explore key challenges the labor movement faces today, and draw lessons from recent activist successes.
The Koch network's long game and its import for progressive organizing / Nancy MacLean -- Right-wing populism, the corporate attack on working Americans and the labor movement response / Gordon Lafer -- Trump, right-wing populism, and the future of organized labor / Bill Fletcher Jr. and Jose Alejandro La Luz -- Walker's Wisconsin and the future of the United States / Jon Shelton -- Whose class is it anyway? : the "white working class" and the myth of Trump / Sarah Jaffe -- Privatization? : chipping away at government / Donald Cohen -- Building a pro-worker, pro-union climate movement / Lara Skinner -- From co-optation to radical resistance : an examination of organized labor's response(s) to immigrant rights in the era of Trump / Shannon Gleeson -- Trumpism, policing, and the problem of surplus population / Cedric Johnson -- Going south : how southern organizing will determine the future of the labor movement / MaryBe McMillan -- Between home and state : care workers and labor strategy for the new open-shop era of Trumplandia / Jennifer Klein -- Fighting and defeating the charter school agenda / Kyla Waters.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 02, 2020).
JSTOR
Keywords: Labor movement -- United States -- History -- 21st century; Labor unions -- Political activity -- United States -- History -- 21st century; Working class -- United States -- History -- 21st century; United States -- Politics and government -- 2017-2021.; Mouvement ouvrier -- États-Unis -- Histoire -- 21e siècle.; Syndicats -- Activité politique -- États-Unis -- Histoire -- 21e siècle.; Travailleurs -- États-Unis -- Histoire -- 21e siècle.; États-Unis -- Politique et gouvernement -- 2017-2021.; POLITICAL SCIENCE / Labor & Industrial Relations; Labor movement; Labor unions -- Political activity; Politics and government; Working class; United States; 2000-2099; Electronic books; History